Visual adaptations of diurnal and nocturnal raptors. (October 2020) - Potier, Simon; Mitkus, Mindaugas; Kelber, Almut
Highlights: Raptors have large eyes allowing for high absolute sensitivity in nocturnal and high acuity in diurnal species. Diurnal hunters have a deep central and a shallow temporal fovea, scavengers only a central and owls only a temporal fovea. The spatial resolution of some large raptor species is the highest known among animals, but differs highly among species. Visual fields of raptors reflect foraging strategies and depend on the divergence of optical axes and on head structures More comparative studies on raptor retinae (preferably with non-invasive methods) and on visual pathways are desirable. Abstract: Raptors have always fascinated mankind, owls for their highly sensitive vision, and eagles for their high visual acuity. We summarize what is presently known about the eyes as well as the visual abilities of these birds, and point out knowledge gaps. We discuss visual fields, eye movements, accommodation, ocular media transmittance, spectral sensitivity, retinal anatomy and what is known about visual pathways. The specific adaptations of owls to dim-light vision include large corneal diameters compared to axial (and focal) length, a rod-dominated retina and low spatial and temporal resolution of vision. Adaptations of diurnal raptors to high acuity vision in bright light include rod- and double cone-free foveae, high cone and retinal ganglion cell densities and high temporal resolution. We point out that more studies, preferably using behavioural and non-invasive methods, are desirable.